Institutionalizing Gender : Madness, the Family, and Psychiatric Power in Nineteenth-Century France - Hewitt, Jessie, 1981- (Book collections on Project MUSE., 2020)
"This book examines the influence of gender and family values on the development of nineteenth-century French psychiatry"--